THE EFFECT OF SERVICE QUALITY, PRICE, AND PROMOTION ON CUSTOMER SATISFACTION AT OPTIK GAGAS UNGARAN - Muhammad Nahrowi; Nurmiyati; M. Arif Rakhman (Jurnal Comparative: Ekonomi dan Bisnis, 2026)
The influence of service quality, price, and promotion on customer satisfaction at Optik Gagas Ungaran is the subject of this research. This study was conducted using a quantitative approach, and the sample consisted of 96 people selected using the Lameshow formula. After data was collected through an online Likert-based questionnaire, SmartPLS version 4.0 was used to conduct a Structural Equation Modeling (SEM) analysis based on Partial Least Squares (PLS). The results of the study indicate that service quality, with a t-value of 4.540 (p=0.000), and price, with a t-value of 6.371 (p=0.000), have a positive and significant effect on consumer satisfaction. Conversely, promotion, with a t-value of 0.372 (p=0.710), does not have a significant effect on consumer satisfaction. The R-square value of 75.4% indicates that the three independent variables can be responsible for variations in consumer satisfaction. Other factors outside the model influence 24.6%. In conclusion, customer satisfaction is greater when service and pricing are more in line with the benefits received. Because promotions that are poorly targeted and unattractive have not proven effective, Optik Gagas Ungaran management is advised to modify its promotional strategy to be more interactive and innovative, ensure competitive and transparent pricing, and increase social media response. Variables such as brand perception or customer trust could be the subject of further research.